Land of wolves [compact disc, unabridged] - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery., 2019)
Wyoming Sheriff Walt Longmire is neck deep in the investigation of what could or could not be the suicidal hanging of a shepherd. With unsettling connections to a Basque family with a reputation for removing the legs of Absaroka County sheriffs, matters become even more complicated with the appearance of an oversize wolf in the Big Horn Mountains to which Walt finds himself feeling more and more empathetic.